NUMERICAL SIMULATIONS FOR THE CASE OF RIGID ROTATING KINEMATIC COUPLING WITH BIG CLEARANCE - Jan-Cristian GRIGORE (Fiabilitate şi Durabilitate)
In this paper an algorithm based on [1] [2] are numerical simulations, achieving generalized coordinates of motion, positions, speeds of a rigid rotating kinematic coupling with big clearance in joint, case without friction